Sensing of Spectrum Holes in Cognitive Radio Networks: A Survey - Randhawa, Navdeep Kaur; Buttar, Avtar Singh (International Journal of Computer Sciences and Engineering, 2014)
Cognitive Radio (CR) has risen as a tempting solution to the problem of spectral inefficiency as it performs sensing of the radio environment, sharing it without harmful interference to Primary Users (PU) and quickly quitting the frequency band if the corresponding licensed user emerges. Spectrum Sensing is the most crucial task for the establishment of cognitive radio based communication mechanism. Challenges related to spectrum sensing are discussed and different sensing techniques are surveyed in this paper along with the analysis of their advantages and disadvantages.